2020
DOI: 10.3390/rs12040691
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing-Based Research for Monitoring Progress towards SDG 15 in Bangladesh: A Review

Abstract: The Sustainable Development Goals (SDGs) have been in effect since 2015 to continue the progress of the Millennium Development Goals. Some of the SDGs are expected to be achieved by 2020, while others by 2030. Among the 17 SDGs, SDG 15 is particularly dedicated to environmental resources (e.g., forest, wetland, land). These resources are gravely threatened by human-induced climate change and intense anthropogenic activities. In Bangladesh, one of the most climate-vulnerable countries, climate change and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 111 publications
(191 reference statements)
0
24
0
1
Order By: Relevance
“…A variety of SDG assessment frameworks have been analyzed with a set of SDGs to monitor progress in different sectors [56][57][58]. Table 2 presents an overview of SDG assessment frameworks used in coastal regions for policy and research purposes in different geographical areas [12,[42][43][44]54,[59][60][61][62].…”
Section: Integrated Coastal Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of SDG assessment frameworks have been analyzed with a set of SDGs to monitor progress in different sectors [56][57][58]. Table 2 presents an overview of SDG assessment frameworks used in coastal regions for policy and research purposes in different geographical areas [12,[42][43][44]54,[59][60][61][62].…”
Section: Integrated Coastal Managementmentioning
confidence: 99%
“…The aim of this study is to tailor the SDGs, as a universally recognized policy framework, to assess the sustainability performance for coastal flood protection management to enhance climate-resilient and adaptable coastal development. The results of a literature review [9,10,23,[25][26][27][28][32][33][34]36,[40][41][42][43][44][45][46] showed a wide range of technical and management adaptation measures towards climate adaption within coastal flood protection management. Some coastal adaptation measures have the potential to play a role in sustainable coastal management, e.g., NBS.…”
Section: Sdg-sis Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing (RS) as the most important information resource plays a role key in the monitoring of our earth (Ishtiaque et al, 2020). Past decades, with the advancement of remote sensing sensor in both spatial and spectral resolution there are a huge interesting in studying hyperspectral imagery in many of fields (Liu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore imperative to harness geospatial information in measuring and monitoring the progress toward SDGs [17][18][19]. In 2017, the Working Group on Geospatial Information of the IAEG-SDGs was established (named as IAEG-SDGs: WGGI) to explore the role of geospatial information and promote its utilization in SDGs monitoring [20].…”
Section: Introductionmentioning
confidence: 99%